Member’s perceptions and expectations of mutual benevolent death fund managed the Malaysian mosque committees - Mustafa, Mohd Ariff; Syed Ibrahim, Sharifah Norhafiza; Bani, Hamidah; Jaaffar, Mohd Yassir; Ali, Kamariah; Mahmud, Radziah; Syed Alwi, Sharifah Faigah (2023)
This study aims to investigate members' perceptions and expectations of the Mutual Benevolent Death Fund managed by Malaysian Mosque Committees. Employing a qualitative research method, the study employs various techniques including interviews, content analysis, and small group discussions to explore beliefs, attitudes, and concepts of normative behavior related to the fund. Purposive sampling is utilized to collect data from participants with specific characteristics, and semi-structured interviews are conducted to examine into the "how" and "why" aspects of their perceptions and expectations. The study follows a four-phase interview protocol framework, ensuring alignment with research questions, constructing an inquiry-based conversation, receiving feedback, and piloting the refined protocol. Data analysis is conducted using ATLAS.ti software, employing techniques such as coding, smart codes, smart groups, and word cruncher to organize and interpret textual and verbal data. Thematic analysis is applied to explore participants' experiences, meanings, and realities, shedding light on current management practices of the Mutual Benevolent Death Fund and contributors' expectations from mosque committees. The results indicate that the majority of members prefer a young and educated leader to manage the fund, primarily due to innovative and creative ideas. The fund committee also needs to clearly understand its role, whether it is solely for providing financial support in case of death or for managing funds in various areas, considering that different preferences exist in different regions.